2015
DOI: 10.1002/anie.201503612
|View full text |Cite
|
Sign up to set email alerts
|

Integrating NiCo Alloys with Their Oxides as Efficient Bifunctional Cathode Catalysts for Rechargeable Zinc–Air Batteries

Abstract: The lack of high-efficient, low-cost, and durable bifunctional electrocatalysts that act simultaneously for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) is currently one of the major obstacles to commercializing the electrical rechargeability of zinc-air batteries. A nanocomposite CoO-NiO-NiCo bifunctional electrocatalyst supported by nitrogen-doped multiwall carbon nanotubes (NCNT/CoO-NiO-NiCo) exhibits excellent activity and stability for the ORR/OER in alkaline media. More imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
231
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(245 citation statements)
references
References 34 publications
11
231
1
2
Order By: Relevance
“…Wu et al reported the combination of NiCo alloys, their oxides and N-doped multiwall carbon nanotubes (NCNT/CoO-NiO-NiCo) as bifunctional ORR/OER catalyst with excellent activity and stability. [107] As expected, the corresponding assembled Zn-air batteries exhibits superior performance to state-of-the-art Pt/C or Pt/C+IrO 2 couple. Also, Chen et al reported the loading of Pt clusters on porous CaMnO 3 nanoparticles with carbon as support as a bifunctional ORR/OER catalyst with excellent activity and durability.…”
Section: Metal/metal Oxide/carbon Compositessupporting
confidence: 65%
“…Wu et al reported the combination of NiCo alloys, their oxides and N-doped multiwall carbon nanotubes (NCNT/CoO-NiO-NiCo) as bifunctional ORR/OER catalyst with excellent activity and stability. [107] As expected, the corresponding assembled Zn-air batteries exhibits superior performance to state-of-the-art Pt/C or Pt/C+IrO 2 couple. Also, Chen et al reported the loading of Pt clusters on porous CaMnO 3 nanoparticles with carbon as support as a bifunctional ORR/OER catalyst with excellent activity and durability.…”
Section: Metal/metal Oxide/carbon Compositessupporting
confidence: 65%
“…4a), the potential at 10 mA cm −2 and Tafel slope of MWNT-PyPBI-Ni x Co 3− x O 4 were respectively ca . 1.54 V and 42 mV dec −1 , comparable to the performance of IrO 2 /C (1.53 V and 56 mV dec −1 ) and the state-of-art OER catalysts in the literature (see Supplementary, Table S2)373839404142. An oxidation current peak at ca .…”
supporting
confidence: 74%
“…The improved electrical conductivity and nanostructure due to the incorporation of Ni into Co 3 O 4 and the hybridizing with pristine MWNTs should be responsible for the enhanced ORR performance12. It is worth noting that the ORR performance of MWNT-PyPBI-Ni x Co 3− x O 4 is close to commercial Pt/C ( E onset,ORR : 0.951 V vs. RHE; E 1/2 : 0.857 V vs. RHE; Tafel slope: 57 mV dec −1 ) and superior to the state-of-art cobalt-based ORR catalysts reported in the literature (Table S3)1314414647. It is considered that the pristine MWNTs form an efficient electron transport network and the well-constructed nanostructure of Ni x Co 3− x O 4 on the MWNT-PyPBI provides a large surface area, leading to the enhanced electrocatalytic performance.…”
mentioning
confidence: 60%
“…These include Fe, Ni and Co and their oxides [15][16][17][18]. Wu and co-workers [19] reported that CoO-NiO-NiCo bifunctional nanocomposites supported by carbon nanotubes exhibited excellent activity and stability towards the ORR and OER in alkaline media. Wei and co-workers [20] prepared cobalt carbonate hydroxide supported on carbon black (CCH/C) via a hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%